Influence of grazing on the activity pattern and temporal niche of two dominant rodent species in Alxa desert - Li, Xin; Yuan, Shuai; Li, Linlin; Zhang, Haoting; Jin, Yonglin; Liu, Lina; Zhang, Rong; Bu, Fan; Sun, Shanshan; Fu, Heping; Wu, Xiaodong (Frontiers in Ecology and Evolution, 2023)
Grazing can potentially affect interspecific interactions by reducing the ecological fitness of animals. Desert rodents are important components in desert ecosystems and indicators of environmental change. Grazing reduces food resources, but rodents can decrease interspecific niche overlap by adaptive behavior. However, the key factors driving rodent behavioral activities and coexistence in the Alxa desert remains unstudied. We monitored population density and behavioral activities of Midday gerbil (Meriones meridianus) and northern three-toed jerboa (Dipus sagitta) in a grazing exclusion experiment in Alxa desert, Inner Mongolia, China, in 2017. We assessed the relationship between environmental factors (such as plant height, density, coverage, rainfall and temperature) and the behavioral activities of two coexisting rodent species. The results showed the following: (1) In summer, grazing significantly reduced the activity time of Midday gerbil compared to that in grazing exclusion areas (F(1,22)=8.702, p <0.01). Grazing reduced the temporal niche overlap with an obvious shifting of activity peaks between two species. (2) Grazing exclusion enhanced the temporal niche overlap between the two rodent species due to greater food availability which relieved inter-specific competition in each season. (3) Grazing strengthened the sensitivity of rodents to environmental changes in all seasons. These results indicated that grazing affected competition between the rodent species by altering vegetation conditions, which in turn affected the temporal niche and activity patterns of rodents.